Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-887
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Gender-Dependent Vowel-Level Analysis for Boosting Speech-Based Depression Recognition

Abstract: Whilst studies on emotion recognition show that genderdependent analysis can improve emotion classification performance, the potential differences in the manifestation of depression between male and female speech have yet to be fully explored. This paper presents a qualitative analysis of phonetically aligned acoustic features to highlight differences in the manifestation of depression. Gender-dependent analysis with phonetically aligned gender-dependent features are used for speech-based depression recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…14). It is obvious from the figure that the accuracy of women is higher than that of men, which is consistent with the results of [24], indicating that gender can affect the classification performance of the model. The results obtained are compared with the results obtained using different machine learning algorithms.…”
Section: Performances On Depression Binary Classificationsupporting
confidence: 85%
“…14). It is obvious from the figure that the accuracy of women is higher than that of men, which is consistent with the results of [24], indicating that gender can affect the classification performance of the model. The results obtained are compared with the results obtained using different machine learning algorithms.…”
Section: Performances On Depression Binary Classificationsupporting
confidence: 85%
“…Specifically, findings revealed a reduced frequency range in vowel production (Darby et al, 1984) and in the speech Vowel Space Area (VSA) (Scherer et al, 2015) in depression. Moreover, gender-dependent vowel level analysis was performed for boosting speech-based depression recognition (Vlasenko et al, 2017). Surprisingly, these studies ignored the speech consonant space.…”
Section: Introductionmentioning
confidence: 99%
“…According to Vlasenko et al [16], performance of depression detection was improved when the feature extraction process was conducted differently depending on gender. In a study by Helfer et al [17], distortions in formant trajectories of speech were shown to be a reliable indication of depression.…”
Section: Introductionmentioning
confidence: 99%